The cost structure of influencers’ posts: the risk of losing followers - Oliveira, Carlos; Garcia, Ana Cristina B; Vivacqua, Adriana S (Personal and ubiquitous computing, 2021)
This paper presents an exploratory study of the posting behavior of digital influencers in social participation platforms. As there are different platforms of social participation, we present a taxonomy to unify the different classifications and delimit the scope of our work. Influencers could produce a positive externality of increasing participation by suggesting social causes and government actions they believe in. However, influencers tend to restrict their posts to the domain subject they became popular for. Our goal is to identify the cost structure of posting behavior of influencers, from the desire to post to the actual act of posting. The findings indicate the two key factors influencers consider when posting are (a) the risk of losing followers and (b) the effort required to verify the information. On the other hand, followers indicate they like it when influencers voice their opinion on social causes. These findings are anchored on social influence theory. We also found different factors that motivate/demotivate people to post on social media. We noticed that the factors that will motivate a user to post can either be aroused in him (i.e., already internalized in the person) or can be “planted” in the person (i.e., from outside).